2011
DOI: 10.1021/ml200202y
|View full text |Cite
|
Sign up to set email alerts
|

Toward Overcoming Staphylococcus aureus Aminoglycoside Resistance Mechanisms with a Functionally Designed Neomycin Analogue

Abstract: Deoxygenation of the diol groups in rings A and D of neomycin in combination with the introduction of an N1-(L)-HABA group in the 2-deoxystreptamine subunit (ring B) leads to a novel and potent antibiotic (1) with activity against strains of S. aureus carrying known aminoglycoside resistance determinants, as well as against an extended panel of Methicillin-resistant S. aureus isolates (n = 50). Antibiotic 1 displayed >64 fold improvement in MIC 50 and MIC 90 against this MRSA collection when compared to the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…Since GenP, GenB3, and GenB4 catalyze C-3′,4′-dideoxygenation, they have the potential to be applied in combinatorial biosynthesis of C-3′,4′-dideoxygenation containing semi-synthetic antibiotics, such as dibekacin and arkekacin [ 36 ], to develop novel drugs against life-threatening pathogens and to yield an improved safety profile [ 37 ]. Because C-3′, C-4′, and C-6′ are frequently used chemical modification sites for semi-synthesis of AGAs [ 38 40 ], GenP, GenB3, and GenB4 may be used for combined chemical and enzymatic syntheses of promising therapeutic leads.…”
Section: Discussionmentioning
confidence: 99%
“…Since GenP, GenB3, and GenB4 catalyze C-3′,4′-dideoxygenation, they have the potential to be applied in combinatorial biosynthesis of C-3′,4′-dideoxygenation containing semi-synthetic antibiotics, such as dibekacin and arkekacin [ 36 ], to develop novel drugs against life-threatening pathogens and to yield an improved safety profile [ 37 ]. Because C-3′, C-4′, and C-6′ are frequently used chemical modification sites for semi-synthesis of AGAs [ 38 40 ], GenP, GenB3, and GenB4 may be used for combined chemical and enzymatic syntheses of promising therapeutic leads.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the exploration of other substituents on N6′ of the neomycin class of 4,5-AGAs may be a fruitful avenue for future explorations both alone and in combination with other recently described modifications known to enhance antibacterial activity. 8,41–49 …”
Section: Discussionmentioning
confidence: 99%
“…5,34,40 Several studies have reported in recent years on the synthesis of improved neomycin derivatives with reduced susceptibility to AMEs, including derivatives of the 6′-amino group. 8,41–49 As demonstrated originally by a Schering-Plough group 45,46 and subsequently exploited by ISIS, 41 and Achaogen 50 6′-amino AGAs can be modified by alkylation of the 6′-amino group to overcome the effects of AAC(6′) AMEs. However, the effects of all these modifications on binding to the eukaryotic mitochondrial ribosomes and, consequently, on the ototoxicity of such derivatives are not known.…”
Section: Introductionmentioning
confidence: 99%
“…This synthetic strategy relied on a novel application of the chemoselective Garegg-Samuelsson deoxygenation reaction in combination with N 1-modifications via oxazolidinones for efficient access to promising antibiotics analogues. 52 Both NEO and PAR were protected with Cbz groups and their primary alcohols were capped with trityl and silyl moieties, respectively. The resulting intermediates retained 6 secondary hydroxyls, 4 of which, involved in trans -diols, were then subjected to deoxygenation to provide intermediates 43 and 45 .…”
Section: Chemical Strategies For the Derivatization/generation Of mentioning
confidence: 99%